Safety of deep brain stimulation in pregnancy: A comprehensive review - King, Caroline; Parker, T. Maxwell; Roussos-Ross, Kay; Ramirez-Zamora, Adolfo; Smulian, John C.; Okun, Michael S.; Wong, Joshua K. (Frontiers in Human Neuroscience, 2022)
Introduction: Deep brain stimulation (DBS) is increasingly used to treat the symptoms of various neurologic and psychiatric conditions. Subjects can undergo the procedure during reproductive years but the safety of DBS in pregnancy remains relatively unknown given the paucity of published cases. We thus conducted a systematic review of the literature to determine the state of current knowledge about DBS in pregnancy and to determine how eligibility criteria are approached in clinical trials with respect to pregnancy and the potential for pregnancy. Methods: A literature review was conducted in EMBASE using search terms to identify all papers with DBS and pregnancy related information. Two reviewers independently analyzed the articles to confirm inclusion. Data extracted for analysis included conditions treated, complications at all stages of pregnancy, neonatal/pediatric outcomes and DBS target. A second search was then conducted using www.clinicaltrials.gov. The same two reviewers then assessed whether each trial excluded pregnant individuals, lactating individuals, or persons of childbearing age planning to conceive. Also assessed was whether contraception had to be deemed adequate prior to enrollment. Results: The literature search returned 681 articles. Following independent analysis and agreement of two reviewers, 8 pregnancy related DBS articles were included for analysis. There were n=27 subjects, n=29 pregnancies (n=2 with subsequent pregnancies), and n=31 infants (n=2 twin pregnancies). There was 1 preterm birth at 35 weeks, and 3 patients who experienced discomfort from the DBS battery (i.e. impulse generator) placement site. All 27 patients had a DBS device implanted before they became pregnant, which remained in use throughout their pregnancy. There was exclusion of pregnant individuals from 68% of 135 interventional trials involving DBS. Approximately 44% of these trials excluded persons of childbearing age not on “adequate contraception” or wishing to conceive in the coming years. Finally, 22% excluded breastfeeding persons. Conclusion: The data from 29 pregnancies receiving DBS treatment during pregnancy was not associated with unexpected pregnancy or post-partum complication patterns. Many clinical trials have excluded pregnant individuals. Documentation of outcomes in larger numbers of pregnancies will help clarify the safety profile and will help guide study designs that will safely include pregnant patients.